2020
DOI: 10.1002/jcp.29990
|View full text |Cite
|
Sign up to set email alerts
|

STAT3‐dependent regulation of the electrogenic Na+/HCO3 cotransporter 1 (NBCe1) functional expression in cortical astrocytes

Abstract: The electrogenic Na + /HCO 3 − cotransporter (NBCe1) in astrocytes is crucial in regulation of acid-base homeostasis in the brain. Since many pathophysiological conditions in the brain have been associated with pH shifts we exposed primary mouse cortical and hippocampal astrocytes to prolonged low or high extracellular pH (pH o) at constant extracellular bicarbonate concentration and investigated activation of astrocytes and regulation of NBCe1 by immunoblotting, biotinylation of surface proteins, and intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…The results also show that the observed change of NBCe1 activity following extracellular metabolic acidosis is not associated with changes of total NBCe1 or surface protein abundance or with activation of astrocytes (Figures 1 and 2). Thus, these results extend our previous observations following exposure of cortical astrocytes to metabolic alkalosis (Khakipoor et al, 2019) or to extracellular acidosis by decreasing extracellular pH at constant bicarbonate concentration (Giannaki et al, 2021). Moreover, the observation that in NBCe1 deficient astrocytes of the rate of alkalinization and acidification was almost abolished, as compared to WT cells (Figure 3) highlights that NBCe1 and not Na + /H + exchanger is the major regulator of intracellular pH in the presence of CO 2 /HCO 3 − in astrocytes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results also show that the observed change of NBCe1 activity following extracellular metabolic acidosis is not associated with changes of total NBCe1 or surface protein abundance or with activation of astrocytes (Figures 1 and 2). Thus, these results extend our previous observations following exposure of cortical astrocytes to metabolic alkalosis (Khakipoor et al, 2019) or to extracellular acidosis by decreasing extracellular pH at constant bicarbonate concentration (Giannaki et al, 2021). Moreover, the observation that in NBCe1 deficient astrocytes of the rate of alkalinization and acidification was almost abolished, as compared to WT cells (Figure 3) highlights that NBCe1 and not Na + /H + exchanger is the major regulator of intracellular pH in the presence of CO 2 /HCO 3 − in astrocytes.…”
Section: Discussionsupporting
confidence: 91%
“…To measure intracellular H + concentration ([H + ] i ) changes in cultured cortical astrocytes in the presence or absence of rapamycin, we used a Visitron imaging system (http://www.visitron.de/) and the acetoxymethyl ester of a proton‐sensitive dye, 2′,7′‐bis‐(carboxyethyl)‐5‐(and‐6)‐carboxyfluorescein (BCECF‐AM), as described previously (Giannaki et al, 2021; Khakipoor et al, 2017, 2019). Cells were incubated with 3 µM BCECF‐AM in bicarbonate‐buffered saline solution for 15 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, NBCe1 protein abundance was determined by immunoblot analysis. Using an antibody raised against NBCe1, strong immunoreactive bands at ~110 kDa and ~130 kDa were detected in cell homogenates of all GBM cellular states, as previously described for mouse hippocampal and cortical astrocytes [ 14 , 15 , 16 ], ( Figure 1 A). These results were further confirmed by immunofluorescence, as shown in Figure 1 B,D.…”
Section: Resultssupporting
confidence: 61%
“…However, we found that blocking p38 MAPK and STAT3 signaling pathways completely eliminated the acute TNF-α application-induced enhancement of Na + currents, but did not influence the increased Nav1.6 protein expression due to longer TNF-α exposure (7 days), suggesting that these two signaling pathways may directly modulate Na + channels in a transcriptional-independent manner. Indeed, previous studies reported that p38 MAPK was involved in the upregulation of different subtypes of Na + currents [ 42 , 69 – 71 ], and activation of STAT3 directly increased the activity of electrogenic Na + /HCO 3 - cotransporter 1 [ 72 ]. However, it was also reported that activation of p38 MAPK reduced the amplitude of peak Nav1.6 currents in the DRG-derived cell line ND7/23 and hippocampal neurons [ 71 , 73 ].…”
Section: Discussionmentioning
confidence: 99%